Kultur unterwegs: Relevanz einer Instanz Reisebilder, Dingwelten, Perspektiven - Schleper, Thomas (Reimer Verlag, 2021)
Why is it that culture nowadays is hardly considered powerful whereas Jacob Burckhardt in his days declared it as a matter of course? 13 experts from a wide range of disciplines seek answers to the question of the relevance of culture during pandemia. Culture can be a vital driver for sustainability, inclusion and democracy. To do so, it needs to take back its relative autonomy, understand itself politically, and be self-critical. What needs to be upheld? And where do we need to examine our tasks in order to bring about a transformation? »Culture on the Move« offers a multi-perspective approach for making one's own judgement.